2016
DOI: 10.1097/md.0000000000002618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Standard Automated Perimetry, Short-Wavelength Automated Perimetry, and Frequency-Doubling Technology Perimetry to Monitor Glaucoma Progression

Abstract: Detection of progression is paramount to the clinical management of glaucoma. Our goal is to compare the performance of standard automated perimetry (SAP), short-wavelength automated perimetry (SWAP), and frequency-doubling technology (FDT) perimetry in monitoring glaucoma progression.Longitudinal data of paired SAP, SWAP, and FDT from 113 eyes with primary open-angle glaucoma enrolled in the Diagnostic Innovations in Glaucoma Study or the African Descent and Glaucoma Evaluation Study were included. Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…These findings suggest that different tests may be able to detect different subsets of patients, just as in glaucoma. 70 72 …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that different tests may be able to detect different subsets of patients, just as in glaucoma. 70 72 …”
Section: Discussionmentioning
confidence: 99%
“…The liberal criterion was the presence of any two test locations signalled as changing with at least one non-edge location. Hu et al 14 found no statistically significant difference in the proportion of progressing and improving eyes across tests using the conservative criterion. Fewer eyes showed improvement on HFA SAP compared with FDT2 using the moderate criterion and FDT2 detected less progressing eyes than HFA SAP using the liberal criterion.…”
Section: Introductionmentioning
confidence: 95%
“…Hu et al 14 compared the performance of HFA SITA-Standard and FDT2 perimetry in monitoring glaucoma progression in 113 eyes of subjects with primary open-angle glaucoma with three criteria (conservative, moderate and liberal). The conservative criterion was the presence of at least three adjacent test locations in the same hemifield signalled as changing with at least one non-edge location.…”
Section: Introductionmentioning
confidence: 99%
“…FDP testing locations have been adjusted to match the Humphrey 24-2 perimetry grid (Humphrey Matrix FDT perimeter, Carl Zeiss Meditec, Dublin, California, USA) allowing for head-to-head comparisons; significant diagnostic correlation was shown (p<0.001 for MD and PSD) [12,129]. Again, FDP technology was able to match and even modestly improve the sensitivity in detecting early glaucomatous damage, [97,110,129,137] however no improvement in monitoring progression of established glaucoma was found [96].…”
Section: Visual Fieldsmentioning
confidence: 99%